Cartographie Des Zones À Risque D’incendies De Forêts À L'aide Du SIG Et La Télédétection Dans L'arrière-Pays Du Port Tanger Med - Maktite, Abderrahim; Faleh, Ali (European Scientific Journal, ESJ, 2017)
Moroccan natural environments, in recent decades, have undergone considerable degradation which is related primarily to the development of populations and the pressure they have exerted on natural resources. One aspect of this degradation is forest fire that has accelerated alarmingly. The study area belongs to the forest area of Tangier which covers an area of 42.000ha. The latter is known for its sensitivity to heat, especially because of the nature of the vegetation cover, weather conditions (frequent and strong wind), and high population density. The present work aims to prioritize the plot study area according to the degree of fire risk of forests using the model established by Dagorne Y. Duche in 1994. To achieve this goal, the application of GIS and Remote Sensing is required to develop a fire risk map in the hinterland of Tangier Mediterranean port.